2014
DOI: 10.1159/000365074
|View full text |Cite
|
Sign up to set email alerts
|

The Opioid System and Brain Development: Effects of Methadone on the Oligodendrocyte Lineage and the Early Stages of Myelination

Abstract: Oligodendrocytes express opioid receptors throughout development, but the role of the opioid system in myelination remains poorly understood. This is a significant problem as opioid use and abuse continue to increase in two particular populations: pregnant addicts (in whom drug effects could target early myelination in the fetus and newborn) and adolescents and young adults (in whom late myelination of ‘higher-order' regions takes place). Maintenance treatments for opioid addicts include the long-lasting opioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 86 publications
5
89
0
Order By: Relevance
“…In medium and high dose methadone-exposed tissue, clusters of undifferentiated cells were evident, which is consistent with findings reported by Vestal-Laborde et al [4], and immature neurons were reported. These effects may be directly related to the smaller than average head circumference seen in human infants prenatally exposed to methadone.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In medium and high dose methadone-exposed tissue, clusters of undifferentiated cells were evident, which is consistent with findings reported by Vestal-Laborde et al [4], and immature neurons were reported. These effects may be directly related to the smaller than average head circumference seen in human infants prenatally exposed to methadone.…”
Section: Discussionsupporting
confidence: 92%
“…Substitution therapy frequently leads to the newborn suffering through neonatal abstinence syndrome [3]. In developing rats, myelination is altered by perinatal exposure to therapeutic doses of methadone [4].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased neuronal counts were obtained in studies using both subcutaneous and intraperitoneal injection during the 2 nd trimester equivalent age [9, 10]. Further studies indicated that therapeutic equivalent doses of subcutaneously-administered buprenorphine and methadone during 2 nd and 3 rd trimester equivalents led to increased myelination and alterations in myelin structure in adolescent rats [11]. While a primary limitation of rodent models is the known differences in metabolism rate relative to humans, consistency of results was obtained in preclinical studies despite differences in animal model and opioid form and dose, suggesting alterations in brain development due to POE.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, opioid receptors are present on neurons, oligodendroglia and astroglia (169), and opioid receptor activation may directly affect neural cell migration and survival (164). In preclinical studies, opioid exposure results in an increase of apoptosis in human neurons and microglia in vitro (168), as well as reduced dendrite length and branching in cortical neurons concomitant with deficits in learning and memory in rodents (134,170,171). Collectively, these data emphasize the detrimental effects of opioid exposure on CNS structure and function.…”
Section: The Effects Of Opioids On the Maternalplacental-fetal Axismentioning
confidence: 99%